2019
DOI: 10.4238/gmr18176
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Predictive ability of AMMI and factorial analytical models in the study of unbalanced multi-environment data

Abstract: Efficient analysis of datasets from multi-environment trials (MET) is of paramount importance in plant breeding programs. Several methods have been proposed for this purpose, each of them having advantages and disadvantages, depending on the objectives of the study. We examined the robustness in the predictive power of models that have been widely used in the study of genotype-byenvironment interaction such as AMMI (additive main-effects and multiplicative interaction) models via EM algorithm, Bayesian AMMI mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Crossa et al [ 30 ] and Perez-Elizalde et al [ 31 ], in turn, showed how to incorporate inference to the AMMI-2 biplot by drawing credibility regions to describe the effect of GEI. The literature also presents further development of this method [ 20 , 32 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Crossa et al [ 30 ] and Perez-Elizalde et al [ 31 ], in turn, showed how to incorporate inference to the AMMI-2 biplot by drawing credibility regions to describe the effect of GEI. The literature also presents further development of this method [ 20 , 32 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…A reference that can serve as a starting point for this study is the comparison made by Romão et al. (2019) of the factorial analytic model with the EM‐AMMI algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional implementations of AMMI and GGE have many limitations associated with the standard method of estimating fixed effects. They do not consider heteroscedasticity, although theoretically, there are procedures based on SVD for the same purpose (Rodrigues et al., 2014; Yan, 2014); however, such procedures are adjusted in two stages and may lead to loss of information (Gogel et al., 2018; Romão et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(2012) empirically demonstrated the flexibility of the Bayesian model to incorporate uncertainty into the AMMI model fitted with two first principal components biplot through bivariate credibility regions built for genotypic and environmental scores, as well as using information from previous experiments incorporated through prior distributions. Other contributions to this method have been recently published (da Silva et al., 2015, 2019; de Oliveira et al., 2015, 2016; Jarquin et al., 2016; Romão et al., 2019).…”
Section: Introductionmentioning
confidence: 99%